2020
DOI: 10.1016/j.virusres.2020.198163
|View full text |Cite
|
Sign up to set email alerts
|

The role of host genetics in susceptibility to severe viral infections in humans and insights into host genetics of severe COVID-19: A systematic review

Abstract: Highlights 40 candidate genes might be associated with severe COVID-19. Inflammasome (NLRP1) as a possible cause of cytokine storm in COVID-19. IL-18, CCR1, CCR9 and EndoU(coronavirus protein) inhibition as possible treatment for COVID-19. DC-SIGN (Lectin pathway) and MxA expression might explain SARS-CoV-2 latency and reactivation in some cases. Case report as study design for discovering novel monogenic cases(with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 83 publications
(102 reference statements)
1
73
0
4
Order By: Relevance
“…The genetic influence on COVID-19 symptoms may reflect the genotype status of candidate genes such as ACE2R, which encodes the target for viral attachment (Hoffmann et al, 2020), and a number of other genes, including those identified in genome-wide association studies (Elhabyan et al, 2020). Another interesting possibility concerns the genetic factors underlying psychological and behavioral traits.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic influence on COVID-19 symptoms may reflect the genotype status of candidate genes such as ACE2R, which encodes the target for viral attachment (Hoffmann et al, 2020), and a number of other genes, including those identified in genome-wide association studies (Elhabyan et al, 2020). Another interesting possibility concerns the genetic factors underlying psychological and behavioral traits.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous clinical manifestations in COVID-19 may be attributed to individual variation in expression not only of ACE2 and TMPRSS2 receptors, but also of genes related to inflammation and immune responses ( Elhabyan et al, 2020 ; Ellinghaus et al, 2020 ; Russo et al, 2020 ; Zhao J. et al, 2020 ). Accordingly, the excessive acute inflammatory responses seen in individuals with severe COVID-19 may lead to MODS and death ( Li H. et al, 2020b ; Wang D. et al, 2020 ).…”
Section: Pathogenesis and Multiple Organ Injury In Covid-19mentioning
confidence: 99%
“…HLA haplotypes have been reported to be associated with the disease susceptibility 25 . A recent meta-analysis revealed that 21 genes involved in toll like receptors and C-lectin pathways were associated with severe COVID-19 26 . Finally, we demonstrated that the onset of improvement of lung radiology might start at the end of the SARS-Cov-2 positive period in nearly all the family clusters.…”
Section: Discussionmentioning
confidence: 99%